2022
DOI: 10.1021/acs.jafc.2c03057
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Metabolic Interactions in a Synergistic Consortium Drive Efficient Degradation of the Herbicide Bromoxynil Octanoate

Abstract: Microbial communities play vital roles in biogeochemical cycles, allowing biodegradation of a wide range of pollutants. Although many studies have shown the importance of interspecies interactions on activities of communities, fully elucidating the complex interactions in microbial communities is still challenging. Here, we isolated a consortium containing two bacterial strains (Acinetobacter sp. AG3 and Bacillus sp. R45), which could mineralize bromoxynil octanoate (BO) with higher efficiency than either stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Moreover, synergistic metabolic interactions between species help to stabilize the communities despite fluctuating environmental conditions or even enhance their functions, and these interactions become stronger when the species are distantly related [ 26 ]. For example, the interspecies interactions between Acinetobacter strain and Bacillus strain in a synergistic consortium resulted in higher degradation efficiency of herbicide bromoxynil octanoate than either strain individually [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, synergistic metabolic interactions between species help to stabilize the communities despite fluctuating environmental conditions or even enhance their functions, and these interactions become stronger when the species are distantly related [ 26 ]. For example, the interspecies interactions between Acinetobacter strain and Bacillus strain in a synergistic consortium resulted in higher degradation efficiency of herbicide bromoxynil octanoate than either strain individually [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Advancement of sequencing technologies alongside the development of automatic pipelines for GSMM construction 31,32 has promoted an increased use of CBM for the modeling of communities with growing complexity [22][23][24]26,33,34 . The relevance of CBM to the study of microbiomes has been demonstrated in a variety of ecosystems and recent works have shown that CBM-based predictions can guide the development of strategies for microbiome management [34][35][36][37] . An accurate representation of microbial metabolic networks depends on the origin of the genomes analyzed.…”
Section: Introductionmentioning
confidence: 99%